Inclusion of canthaxanthin and 25-hydroxycholecalciferol in the diet of broiler breeders on performance and incubation parameters - Duarte,Vinicius (2015)
The objective of this experiment was to evaluate the effects of a diet containing canthaxanthin and 25-hydroxycholecalciferol (25-OH-D3) on the production and reproductive performances of Cobb 500 broiler breeders aged 53 to 61 weeks. The study included 36,000 Cobb 500 female and 3,600 male broiler breeders aging 51 weeks. The birds were housed in three poultry houses divided into four plots, totaling 12 experimental units each containing 3,000 females and 300 males. The birds received the following treatments: control diet (without the studied additives) or the control diet with the addition of 60mg kg-1feed of 25-(OH)-D3 and canthaxanthin feed (6mg of canthaxanthin and 2,760,000IU of 25-(OH)-D3 per kg of feed) per the supplier's recommendations. The experimental design used was a randomized complete block design with two treatments and six replicates. The results were subjected to analysis of variance followed by the F-test. The treatments had no effect on egg production, usability of eggs and number of incubatable eggs per bird housed. The inclusion of canthaxanthin and 25-(OH)-D3 in the diet reduced embryonic mortality while increasing egg yolk pigmentation, hatching percentage, and number of viable chicks produced per bird. Therefore, the use of 60mg kg-1of 25-(OH)-D3 plus canthaxanthin is recommended in the diet of Cobb 500 broiler breeders aging 53 to 61 weeks to improve important reproductive traits that have great economic impacts on poultry farms